HUBUNGAN KEKUATAN GENGGAMAN DAN KELENTUKAN OTOT PUNGGUNG DENGAN HASIL KETEPATAN SERVIS ATLET TENIS LAPANGAN PUTERA PPLP PROVINSI RIAU - M.Nurul Fathoni; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This problem in this study is when athletes servicing and contact between racket with the ball, unstable position and rocking racket, and not precisely target the ball into the service box because the results of the rate of the ball when the service does not fall sharply. This study aims is to determine whether there is a corelation of grip strength and back muscles flexibility with the accuracy of service by man tennis athlete of riau province pplp. Sample collections tecnique is total sampling the population of this study are a man tennis athlete of riau province pplp, the sample of this study were man tennis athlete of riau province pplp with the numbered of athletes are 4 athletes. This research using a correlation technique. Then, the data are tested using the test of normality, test the product moment correlation test, multiple correlation test. Test of normality of variabels X1, L0maks (0,218) < Ltabel (0,381), test of normality of variabels X2, L0maks (0,242) < Ltabel (0,381), and testing normality of variabels Y, L0maks (0,261) < Ltabel (0,381) in other words at an of normal data and concluded the results showed: there is a relationship between grip strength with accuracy of tennis service, with correlation rx1y= 0,84, which is based on the correlation coefficient table has a very strong relationship level. Thus, Ho rejected and Ha accepted. There is a relationship between back muscles flexibility with accuracy of tennis service, with correlation rx2y= 0,60, which is based on the correlation coefficient table has a strong relationship level. Thus, Ho rejected and Ha accepted. There is a relationship between grip strength and back musles flexibility with accuracy of tennis service, with correlation R= 0,74, which is based on the correlation coefficient table has a strong relationship level.Key Words: Grip Strength, Back Muscles Flexibility, Accuracy of Tennis Service